„Wie die Geschichtsschreiber der Welt die Geschichte des Felsens schreiben“. Die zerschlagene Gedächtnislandschaft in der „Saison in den Alpen“ von Mieczysław Jastrun - Elżbieta Dutka (Góry, Literatura, Kultura)
Mieczysław Jastrun stayed with a group of Polish painters and writers in Switzerland for three winter months between 1946 and 1947. After his return, the poet published A Season in the Alps and Other Poems (1948). The unconventional and undescriptive mountain landscapes presented in it were influenced by fresh war memories and anxieties related to the new political situation in Europe. Jastrun’s lyrical works refer to the well-known mountain symbolism and play with topoi, but despite this, there is a clear distance from tradition, especially the Romantic one. The article analyses the image of mountain space evoked in the poem A Season in the Alps, in the context of Alpine literature and using the tools suggested by geopoetics. Particular attention is paid to the texture of place in which the archive of culture plays a dominant role. Numerous tropes and figures (e.g. the metaphors “chronicles of the earth” and “a book bound with stone snaps” referring to the mountains) and allusions to Słowacki’s poem In Switzerland make the Alps in Jastrun’s poem not only a “place touched by autobiography” (per M. Czermińska), discovered during a short stay. “The peaks of old Europe” evoke the past and is a landscape of memory built by intertextual references. However, the confrontation of cultural memory with reality reveals not a community but a conflict. It generates a sense of alienation and reluctance/resentment. The broken, decomposed Alpine landscape of memory evoked in A Season in the Alps morphs into a question about history and its meaning. It also expresses fears related to the fragility of human existence and simultaneously signals the need to search for a new poetic language, giving the poem a self-referential character.